Identifying Provinces With RMNCH-IC Disparities Between Urban - Rural Residences In Indonesia - Satria, Manca; Nooraeni, Rani (Poltekkes Kemenkes Surakarta, 2023)
Background: Intervention coverage in reproductive, maternal, newborn, and child health (RMNCH-IC) is still unequal between urban and rural residences. This inequality is considered to also occur in Indonesia. The Composite Coverage Index (CCI) measures RMNCH-IC. However, CCI measurements at provincial levels according to residences are not yet available in Indonesia due to the limited sample size at some CCI indicators. Therefore, provinces with a large RMNCH-IC inequality, or disparity, between residences have not been identified. Thus, this study aims to measure CCI as a whole at provincial levels according to residences in Indonesia through the estimation of CCI indicators using MRP, to be used to identify provinces with CCI disparities between residences. Methods: Small Area Estimation (SAE), especially Multilevel Regression and Poststratification (MRP) models, can be used to estimate parameters for each province according to residences with limited samples. The secondary data used in this study come from the latest survey, the 2017 Indonesian Health Demographic Survey (IDHS). Results: Based on the value of the CCI dimension, urban residences have better dimensions of maternal and newborn health, while rural residences have better dimensions of reproductive and child health. There are 5 provinces with RMNCH-IC disparities between residences in Indonesia. Conclusion: Efforts to reduce CCI inequalities are still needed for each residence in their respective dimension, especially for provinces with RMNCH-IC disparities. Further research is needed to explain the determinants of the large disparities between the five provinces.